Extracorporeal membrane oxygenation in acute respiratory distress syndrome caused by elderly tuberculous meningitis: a case report and review of the literature - Shi, Zhaokun; Zhu, Xue; Gao, Wenwei; Yu, Shuhui; Zhan, Liying (Frontiers in Medicine, 2024)
patient was conscious and could communicate with family members as normal.levels, he was placed on veno-venous ECMO for 8 days. On the 47th day, the tracheotomy catheter was pulled out and sealed. The Without positive results of mNGS and culture, anti-tuberculosis (TB) treatment was started. In order to improve oxygenation was admitted with a fever and shaking. Despite aggressive initial treatment, the patient progressed rapidly and developed ARDS. detection of atypical, rare pathogens in clinical specimens. We report a case of a 65-year-old man with ARDS caused by TBM. He extracorporeal membrane oxygenation (ECMO). Besides, metagenomic next-generation sequencing (mNGS) can facilitate the syndrome (ARDS), an inflammatory lung injury, can be treated by mechanical ventilation, fluid management, and even (CSF) is an important diagnostic tool for patients with suspected central nervous system (CNS) diseases. Acute respiratory distress Diagnosing and clinical management of tuberculous meningitis (TBM) are still challenging for clinicians. Analysis of cerebrospinal fluid